Association of combined healthy lifestyle with general and abdominal obesity - Sadeghi, Omid; Eshaghian, Niloofar; Keshteli, Ammar Hassanzadeh; Askari, Gholamreza; Esmaillzadeh, Ahmad; Adibi, Peyman (Frontiers in Nutrition, 2024)
Background Data linking joint healthy lifestyle factors to general and abdominal obesity are scarce, in particular in the Middle East. The aim of this study was to examine the association of combined healthy lifestyle factors with general and abdominal obesity in a large population of Iranian adults. Methods This cross-sectional study was done on 3,172 Iranian adults aged ≥18 years. We constructed healthy lifestyle score using information on dietary intakes, physical activity, smoking status, and psychological distress. To evaluate components of healthy lifestyle, we applied a validated 106-item semi-quantitative Food Frequency Questionnaire (FFQ), General Practice Physical Activity Questionnaire (GPPAQ), General Health Questionnaire (GHQ), and other pre-tested questionnaires. General obesity was defined as having a body mass index (BMI) ≥30 kg/m2 and abdominal obesity as a waist circumference (WC) of ≥102 cm in men and ≥88 cm in women. Results Mean age of participants was 36.54 ± 7.97 years. General and abdominal obesity were prevalent among 8.7% and 21.5% of study participants, respectively. Linear analysis showed a significant positive relationship between healthy lifestyle score and BMI among men (β: 0.30, 95% CI: 0.05, 0.54). However, no significant association was found between healthy lifestyle and abdominal obesity in men. Among women, one score increase in healthy lifestyle score was associated with a reduction of 0.65 cm in WC. In terms of individual components of healthy lifestyle, we found that low-distressed women had lower odds of abdominal obesity compared with high-distressed women. Conclusion We found a significant inverse association between healthy lifestyle and WC among women. However, healthy lifestyle was positively associated with BMI among men.